Tetrameres fissispina Infection in Local Chickens in Taraba State, Nigeria, Case Report - Kamani, J.; Meseko, C.A.; Tanko, T.J.; Tafarki, A.E.; Lazarus, D.D.; Peter, J.G.; Oladokun, T. (International Journal of Poultry Science, 2008)
A severe and fatal outbreak of Tetrameres fissispina in four flocks of local chickens in Nigeria is being described. The outbreak was characterized by sudden and massive death and pathology mimicking avian influenza. Convention tests for major viral and bacterial diseases of poultry in Nigeria were all negative. T. fissispina was isolated from most carcasses submitted for post mortem examination. A pathogenic T. fissispina in local chicken is being reported